2022
DOI: 10.7547/21-114
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of a Diabetic Foot Infection Caused by Staphylococcus pseudintermedius, a Zoonotic Pathogen of Canine Origin

Abstract: Staphylococcus pseudintermedius is an emerging zoonotic pathogen that is very similar to human Staphylococcus pathogens, particularly multidrug-resistant Staphylococcus aureus. Recent reports have indicated that S pseudintermedius is easily transmitted between pets (mainly dogs) and owners because of these similarities. Although this pathogen has been associated with diabetic foot infections, it has not yet been described in the podiatric medical literature. In this case report, we present a diabetic foot infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Methicillin-resistant Staphylococci are considered as important pathogens worldwide [ 7 , 8 ]. They can persist in animals and various environments [ 9 ] for prolonged periods, and potentially infect humans [ 10 ]. Genomic analysis revealed that Staphylococci species originating from different hosts and environments can mutually exchange several resistance factors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methicillin-resistant Staphylococci are considered as important pathogens worldwide [ 7 , 8 ]. They can persist in animals and various environments [ 9 ] for prolonged periods, and potentially infect humans [ 10 ]. Genomic analysis revealed that Staphylococci species originating from different hosts and environments can mutually exchange several resistance factors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%